2016
DOI: 10.1039/c6ta04577d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multi-component nanofiber separators for lithium polysulfide capture in lithium–sulfur batteries: an experimental and molecular modeling study

Abstract: A multi-functional nanofiber membrane significantly improves the overall performance of Li–S batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…As shown in some studies, the introduction of a functional layer between the cathode and anode increased the consumption of electrolyte by forming an solid‐electrolyte interface layer and/or wetting the additional surface of the functional layer, resulting in an increase in the electrolyte use. A recent study reported that the incorporation of functional layers of PAN and SiO 2 increased the uptake of the electrolyte to 330% . The specific electrolyte loadings in recent studies were 40, 50, 60, 80, and 100 µL mg −1 , respectively .…”
Section: Perspectives For Functional Interlayers/separators Of Li–s Bmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in some studies, the introduction of a functional layer between the cathode and anode increased the consumption of electrolyte by forming an solid‐electrolyte interface layer and/or wetting the additional surface of the functional layer, resulting in an increase in the electrolyte use. A recent study reported that the incorporation of functional layers of PAN and SiO 2 increased the uptake of the electrolyte to 330% . The specific electrolyte loadings in recent studies were 40, 50, 60, 80, and 100 µL mg −1 , respectively .…”
Section: Perspectives For Functional Interlayers/separators Of Li–s Bmentioning
confidence: 99%
“…The heteroatom and functional groups on carbon materials showed insufficient interactions with the polysulfide species below 2 eV . On the other hand, SiO 2 interacts with polysulfide species, ranging from above ≈2 eV to ≈3 eV . The interaction energies of MoS 2 with polysulfide species are ≈3–5 eV, making it a good candidate for a PS‐anchoring material .…”
Section: Ps‐functionsmentioning
confidence: 99%
“…The batteries incorporating this PEDOT/PPS modified separator exhibit a discharge capacity of 985 mAh g −1 with a capacity decay rate of 0.0364% per cycle during 1000 cycles at 0.25 C , superior to those with commercial separators (981 mAh g −1 , 0.0932%). Zhu et al prepared a polyacrylonitrile‐silica/MWCNT separator via electrospinning. In this separator, CN and SiO 2 trap the polysulfide through chemical interaction and MWCNT provides electrons for the polysulfide reduction reaction.…”
Section: Separators To Restrain Polysulfide Shuttle Effectmentioning
confidence: 99%
“…The most commonly used inorganic nanoparticles are SiO 2 , TiO 2 , zinc oxide (ZnO), calcium carbonate (CaCO 3 ), etc. The Zhu's research team prepared a multifunctional PAN/SiO 2 nanofiber membrane with an integral ultralight and thin multiwalled CNT sheet, which was beneficial for the fleet diffusion of both Li‐ions and electrons and inhibition of the diffusion of polysulfides. A superior capacity retention of 741 mAh g −1 at 0.2 C after 100 cycles with excellent performance was obtained even with a large S content of 70 wt%.…”
Section: Separatormentioning
confidence: 99%